Stagnation of a "Miracle": Botswana's Governance Record Revisited - Christian von Soest (German Institute of Global and Area Studies (GIGA), 2009)
Botswana has been dubbed an 'African miracle'. The country has been praised not only for maintaining a multiparty system and high growth rates since independence but also for its good governance record. In contrast to other African countries, the extent of neopatrimonialism, which runs counter to good governance, is said to be low. This article aims to a) precisely assess Botswana's neopatrimonial profile and b) put forward explanations for the comparatively low level of neopatrimonialism and for the recent 'stagnation of a miracle'. The paper finds that there have always been neopatrimonial tendencies in Botswana, though they have been largely overlooked by mainstream analyses. The crucial difference is the limited nature of these tendencies relative to other African countries. This can be attributed to the independence period, characterized by the homogeneity of political, economic, and administrative interests in safeguarding private property rights through a 'strong' rational-legal state, that is, by limiting neopatrimonialism. Financed by massive revenues stemming from diamonds, the Southern African Customs Union (SACU), and the Bank of Botswana, the government of the Botswana Democratic Party (BDP) was able to secure its reign through the provision of public goods and limited neopatrimonial exchange relations. However, due to decreasing electoral dominance and elite cohesion, the ruling party is now reverting to some neopatrimonial and authoritarian means in order to safeguard its rule. – – Oftmals wird Botswana als 'afrikanisches Wunder' bezeichnet. Das Land wird nicht nur für seine Mehrparteiendemokratie und sein hohes Wirtschaftswachstum seit der Unabhängigkeit geschätzt, sondern auch für gute Regierungsführung. Im Gegensatz zu anderen afrikanischen Ländern wird der Umfang von Neopatrimonialismus, der guter Regierungsführung entgegensteht, für niedrig gehalten. Um dies zu überprüfen, verfolgt dieser Artikel zwei Ziele: 1) die systematische Erfassung von Botswanas neopatrimonialem Profil und 2) die Erklärung des vergleichsweise niedrigen neopatrimonialen Niveaus des Landes und der 'Stagnation des Wunders' in jüngster Zeit. Es zeigt sich, dass in Botswana schon immer neopatrimoniale Tendenzen bestanden haben, die in den meisten Analysen übersehen werden. Jedoch sind diese Tendenzen begrenzter als in anderen afrikanischen Ländern. Von besonderer Bedeutung ist dabei die Zeit der Unabhängigkeit, die durch die Homogenität politischer, ökonomischer und administrativer Interessen gekennzeichnet war. Die Elite unterstützte die Garantie von Eigentumsrechten durch einen starken Staat. Der Abbau von Diamanten, die Überweisungen der Zollunion des Südlichen Afrikas (SACU) und die Profite der Zentralbank erbrachten zudem hohe Staatseinnahmen, mit denen die Regierung öffentliche Güter finanzieren konnte. Dies stabilisierte die Herrschaft der seit der Unabhängigkeit amtierenden Regierungspartei Botswana Democratic Party (BDP). Jedoch nehmen ihre Dominanz bei Wahlen sowie die Elitekohäsion in jüngster Zeit spürbar ab. Als Reaktion darauf bedient sich die herrschende Elite nun einiger neopatrimonialer und autoritärer Mittel, um ihre Herrschaft zu sichern.
Keywords: 300; neopatrimonialism; corruption; governance; institutions; interests; development; Botswana